Anyone can create an app : beginning iPhone and iPad programming - Wise, Wendy L. (Manning Publications, 2017)
Do you have a fantastic idea for an iPhone app but no idea how to bring it to life? Great news! With the right tools and a little practice, anyone can create an app. This book will get you started, even if you've never written a line of computer code. About the Book Anyone Can Create an App begins with the basics by introducing programming concepts, the Swift language, and the tools you'll need to write iOS apps. As you explore the interesting examples, illuminating illustrations, and crystal-clear step-by-step instructions, you'll learn to Get started programming, no experience necessary! Add controls like text boxes and buttons Keep track of your favorite things by creating the Like It or Not (LioN) app By the end, you'll be able to create and run your own apps, and you'll have the confidence to learn more on your own. The book is updated for Swift 3. About the Reader This book is written especially for non programmers — no experience needed! About the Author Wendy Wise has an extensive background in mobile and application development and has worked with several Fortune 500 companies. In her 17-year technical career, Wendy has served as a senior director of software development, a senior product manager for international mobile applications, and a hands-on developer for web and mobile technologies, among many other technical roles. Wendy fully embraces her nerd/geek side, as you'll find out as you read this book. In her spare time, she enjoys beer, coffee, photography, camping, and being outdoors.